Pengaruh Pijat Endorfin terhadap Tingkat Kecemasan Inpartu Kala I Fase Laten di Puskesmas Gesang Kabupaten Lumajang - Mualimah, Sa'iratul; Retnaningsih, Reny; Purwati, Anik (Journal of Issues in Midwifery, 2024)
Endorphin massage is known to help reduce anxiety in laboring mothers by stimulating the body’s natural pain-relief mechanisms. This study aims to assess the effectiveness of endorphin massage in reducing anxiety levels in mothers during the latent phase of labor (stage 1). The research focuses on determining the difference in anxiety levels before and after receiving the massage. This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 mothers in the latent phase of labor at Puskesmas Gesang, selected through purposive sampling. Anxiety levels were measured using a validated anxiety scale before and after the 20-minute endorphin massage. The message targeted specific areas known to stimulate the release of endorphins, such as the shoulders and lower back. The results showed a significant reduction in anxiety levels following the endorphin massage intervention. The average anxiety score before the intervention was 7.5, which decreased to 4.0 after the massage (p < 0.05). This indicates that endorphin massage has a positive effect on reducing anxiety in mothers during the latent phase of labor. Endorphin massage is an effective method to alleviate anxiety in laboring mothers during the latent phase. The intervention provides a non-invasive, simple, low-cost option that can be easily implemented in primary healthcare settings. Endorphin massage should be incorporated into routine maternity care, especially during the early stages of labor, to promote maternal relaxation and potentially improve labor progression and outcomes. Keywords: Endorphin massage, maternal anxiety, latent phase labor, laboring mothers, anxiety reduction.